Expression of Estrogen Receptor Alpha in Malignant Melanoma - Parvin Rajabi; Marzieh Bagheri; Mohsen Hani (Advanced Biomedical Research, 2017)
Background: Features of malignant melanoma (MM) vary in the different geographic regions of the world. This may be attributable to environmental, ethnic, and genetic factors. The aim of this study was to determine the expression of estrogen receptor alpha (ER-α) in MM in Isfahan, Iran. Materials and Methods: This study was planned as a descriptive, analytical, cross-sectional investigation. During this study, paraffin-embedded tissue blocks of patients with a histopathologic diagnosis of MM was studied for ER-α using immunohistochemistry (IHC). Results: In this study, 38 patients (female/male; 20/18) with a definite diagnosis of malignant cutaneous melanoma and mean age of 52.4 ± 11.2 years were investigated. Using envision IHC staining, there were not any cases with ER-α expression. Conclusion: In confirmation to the most previous studies, expression of ER-α was negative in MM. It is recommended to investigate the expression of estrogen receptor beta and other markers in MM.